The Role of Childhood Executive Function in Explaining Income Disparities in Long‐Term Academic Achievement. Issue 5 (25th July 2020) - Deer, LillyBelle K.; Hastings, Paul D.; Hostinar, Camelia E.
Abstract : This study utilized data from the Avon Longitudinal Study of Parents and Children ( N = 14, 860) to examine whether early‐life family income (age 0–5) predicted long‐term academic achievement (age 16–18) and to investigate the role of executive function (EF) assessed multiple times across age 7–11 in explaining this association. Task‐based EF was a significant mediator between early‐life family income and later academic achievement in every model. This mediating pathway persisted when adjusting for a comprehensive panel of covariates including verbal IQ, sex, family income at ages 8 and 18, and early‐life temperament. Additionally, teacher‐rated and parent‐rated EF mediated in some models. Overall, these findings suggest that childhood EF may play an important role in perpetuating income‐based educational disparities.